New record of Paralomis spinosissima Birstein & Vinogradov (Decapoda: Anomura: Lithodidae) from Mar del Plata, Argentina - Olguin, Nicole; Ocampo, Emiliano Hernan; Farias, Nahuel Emiliano (Zootaxa)
The lithodid crab Paralomis spinosissima is previously known only in Sub-Antarctic waters from South Georgia Islandto the Drake Passage. Here we recorded a juvenile male obtained off shores of Mar del Plata (~37°S), Argentina. This newoccurrence extends the distribution range of the species over 1300 km northwards in the Atlantic Ocean. Fil: Olguin, Nicole. Universidade de Sao Paulo; Brasil Fil: Ocampo, Emiliano Hernan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Farias, Nahuel Emiliano. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina